Pengaruh Penguasaan Kosakata terhadap Pemahaman Isi Wacana pada Siswa Kelas V SD Se-Kecamatan Banyumas Tahun Ajaran 2020/2021 - Ratna Handayani Pramukti; Ngatman Ngatman; Muhamad Chamdani (Universitas Sebelas Maret, 2021)
The study aimed to determine the positive effect of vocabulary mastery on understanding the discourse to fifth grade students of public elementary schools in Banyumas Sub-district in academic year of 2020/2021 and to measure the contribution of vocabulary mastery on understanding the discourse to fifth grade students of public elementary schools in Banyumas Sub-district in academic year of 2020/2021. The research was correlational quantitative approach. Sampling technique was probability sampling cluster random sampling. Pearson Product Moment correlation analysis with results obtained correlation coefficient value of 0.579 and Sig value. 0,000<0.05. It meant that vocabulary mastery gave positive and significant effect on understanding the discourse to fifth grade students of public elementary schools in Banyumas Sub-district in academic year of 2020/2021 and the correlation was moderate. Vocabulary mastery contributed 33.5% on understanding the discourse and the remaining 66.5% by other factors. It concludes that there is positive and significant effect of vocabulary mastery on understanding the discourse to fifth grade students of public elementary schools in Banyumas Sub-district in academic year of 2020/2021. The richer the mastery of student vocabulary, better the understanding of the content of discourse in students, and vice versa.